Exhaust Gas Emissions of Homogeneous Gasoline-Methanol-(Ethanol) Blends - Budi Waluyo; Bagiyo Condro Purnomo (Automotive Experiences, 2022)
In recent years, one of the most logical efforts made to reduce the dependence on fossil energy sources is the use of a gasoline-methanol fuel blend. However, the problem in using a gasoline-methanol blend as fuel is that the methanol will eventually separate itself from the gasoline unless they are properly blended together, this is because methanol has a polar hydroxyl group called monohydric that binds water vapor together, causing the mixture to separate. Previous research showed that adding a small amount of ethanol to the gasoline-methanol blend makes it a homogeneous blend. Therefore, this research aims to identify the exhaust emissions of the homogenous gasoline-methanol-(ethanol) blend. For each blended fraction was tested on a single-cylinder four-stroke engine. The emission test is carried out in two stages which include the gasoline mode, and the alcohol mode. These two measurement modes undergo a validation process to correct the differences in the measurement results of the gasoline-methanol-ethanol blends. The test results show that increasing the methanol fraction in the gasoline-methanol-(ethanol) fuel blend results in reduced emission of carbon monoxide and unburnt hydrocarbon because methanol has a high enthalpy of evaporation, which increases both volumetric efficiency and complete combustion. In addition, the increase in the methanol fraction in the gasoline-methanol-(ethanol) blend showed a higher increase in carbon dioxide emissions. This is because methanol and ethanol have a much lower energy content than gasoline. Therefore, its energy production per unit time requires more fuel molecules.